Language analysis of spontaneous descriptions of restless legs syndrome: Gender differences?. (8th July 2021) - Holzknecht, Evi; Domahs, Frank; Brandauer, Elisabeth; Bergmann, Melanie; Zengin, Tugba; Delazer, Margarete; Hochleitner, Margarethe; Högl, Birgit; Stefani, Ambra
Summary: Patients with restless legs syndrome (RLS) use various terms when describing their symptoms. Whether gender might influence this has not been investigated so far. The aim of this study was to evaluate possible gender differences in spontaneous descriptions of RLS symptoms. This prospective study, conducted in 100 consecutive German‐speaking RLS patients, used a single standardized question. Answers were digitally recorded and transcribed. A content‐related linguistic analysis of the transcripts was performed by two independent blinded raters. The lengths of the answers and content‐related linguistic features were compared between women and men. Ninety‐eight patients were included in the final analysis, 59 women (60.2%) and 39 men (39.8%), with a median age of 62 (23–94) and 63 (31–82) years, respectively ( p = 0.602). Demographic and clinical features, including educational level and RLS treatment class, did not differ between genders ( p > 0.05). Total word or sentence count showed no gender differences ( p = 0.159 and 0.259, respectively), although men used more words per sentence than women ( p = 0.018). More men than women described quiescegenic (i.e., triggered by rest or inactivity) symptoms ( p = 0.006) and successful attempts at relief ( p = 0.039). There was a non‐significant trend toward a more frequent use of the first‐person perspective in men (median times used = 5 [0–10.5] vs. 3.8 [0–17.5], p = 0.068). The more frequent mention of quiescegenic symptoms and successful attempts at relief in men could indicate differences in phenotypic presentation of RLS between genders, a more precise description of RLS symptoms or a higher experience of self‐efficacy in men compared to women.